Direct optical second harmonic generation probing of manufactured effect at interfaces between high-κ dielectric and silicon - Yue Fu; Ruichen Niu; Hongda Zhao; Guangtong Jiang; Kunpeng Zhang; Zhe Zhang; Siwei Zhang; Junbin Li; Ran Wang; Zichen Zhang (AIP Advances)
The selection of fabrication method is essential in dielectric layer fabrication of the field-effect transistors. In this study, the second harmonic generation (SHG) signals are observed from the interfaces between high-κ dielectric layers fabricated by different methods and silicon substrate, a promising class of silicon-based microelectronic and optoelectronic applications. We show that the SHG signals of these interfaces critically depend on the fabrication temperature and dielectric layer thickness. The density and polarity of charges between Si and high-κ dielectric can be controlled through interlayer thickness tuning, which can be evaluated based on the SHG signals. At high fabrication temperature, it is determined by multiple-photon-induced charge trapping indicated by a conduction band offset. We attribute the change in time-dependent second harmonic generation to the additional contribution of the electric field generated within the near-surface region at the interface, which is induced by light. Our findings, therefore, highlight the advantage of SHG, which is noninvasive, contactless, and sufficiently sensitive to the defects of the centrosymmetric semiconductor interface via optical methods and could be utilized for non-contact characterization.